Peran Administrasi Sekolah dalam Meningkatkan Efektivitas Operasional dan Kualitas Pendidikan Islam - Fatoni, Mahfud Heru; Fatimah, Meti; Santoso, Baron; Syarifuddin, Hamid (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
School administration plays a very important role in carrying out the basic functions of Islamic educational institutions. . The purpose of this study is to identify the role of school administration in improving the operational effectiveness and quality of Islamic education. This study uses a library research method, which aims to collect, analyze, and compile information from various literature sources in order to obtain a comprehensive understanding of the topic being studied. The data analysis technique used is descriptive-qualitative. The results of the study show that the role of school administration is very important in improving the operational effectiveness and quality of Islamic education. Good administration is not only about technical management, but also about creating an environment that supports the development of students' morals and spirituality. With effective administration, schools are expected to be able to provide Islamic education that is not only academically qualified, but can also shape students' characters in accordance with Islamic values. It is hoped that this study can be a reference for policy makers and practitioners of Islamic education in formulating better management strategies, so that they can improve the quality of Islamic education as a whole.